Architectural graphics - Ching, Francis D. K. (John Wiley & Sons, 2009)
Preface -- Drawing tools and materials -- Architectural drafting -- Architectural drawing systems -- Multiview drawings -- Paraline drawings -- Perspective drawings -- Rendering tonal values -- Rendering context -- Architectural presentations -- Freehand drawing -- Index.; Includes index